2012
DOI: 10.1186/1471-2334-12-204
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial brain abscess in patients with nasopharyngeal carcinoma following radiotherapy: microbiology, clinical features and therapeutic outcomes

Abstract: BackgroundThis study aimed to analyze the clinical features, causative pathogens, neuro-imaging findings, and therapeutic outcomes of bacterial brain abscess in patients with nasopharyngeal carcinoma (NPC) following radiotherapy.MethodsNPC patients with bacterial brain abscess were evaluated. Their clinical data were collected over a 22-year period. For comparison, the clinical features, causative pathogens, neuro-imaging findings, and therapeutic outcomes between NPC and non-NPC patients were analyzed.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In our patient, a defective CNS barrier owing to previous radiotherapy for NPC may have given the microorganism(s) easy access to the intracranial space. This hypothesis is supported by one study that found a high concurrence of bacterial brain abscess and chronic otitis media in NPC patients following radiotherapy [6].…”
Section: Discussionmentioning
confidence: 73%
“…In our patient, a defective CNS barrier owing to previous radiotherapy for NPC may have given the microorganism(s) easy access to the intracranial space. This hypothesis is supported by one study that found a high concurrence of bacterial brain abscess and chronic otitis media in NPC patients following radiotherapy [6].…”
Section: Discussionmentioning
confidence: 73%
“…Although extensive studies of central nervous system (CNS) infection have been performed in postradiotherapy NPC patients, subdural empyema is very rare, and only one case has been previously described in detail[ 3 - 5 ]. This previous study demonstrated that postradiotherapy NPC patients are prone to CNS infection for the following reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Misplaced central lines in all these locations have been reported and have not usually resulted in serious consequences except in the case of pericardiophrenic vein. Misplacement of the large dialysis catheter in these locations has been reported [5,6] and can have dangerous consequences such as hemothorax, pneumothorax, hemopericardium, cardiac tamponade etc. Even though entry of catheter into a planned vein can be ensured using ultrasound, its subsequent passage cannot be controlled.…”
Section: Discussionmentioning
confidence: 99%